Mephedrone, Methylone and 3, 4‐Methylenedioxypyrovalerone (MDPV) Induce Conditioned Place Preference in Mice. (6th May 2014) - Karlsson, Louise; Andersson, Mikael; Kronstrand, Robert; Kugelberg, Fredrik C.
Abstract During the last decade, there has been a worldwide increase in popularity and abuse of synthetic cathinones. Common ingredients of the so‐called bath salts include mephedrone, methylone and 3, 4‐methylenedioxypyrovalerone (MDPV). Relatively little information about the pharmacology and addiction potential of these drugs is available. We used the conditioned place preference (CPP) paradigm to explore the reinforcing effects of three different synthetic cathinones. The primary aim of this study was to investigate whether mephedrone, methylone and MDPV induce CPP in mice. The secondary aims were to investigate a possible dose–response CPP and whether the synthetic cathinones induce higher CPP than amphetamine at equal dose. C57BL/6 mice were conditioned to mephedrone, methylone, MDPV and amphetamine at doses of 0.5, 2, 5, 10 or 20 mg/kg (i.p.). During the conditioning, the mice received two training sessions per day for 4 days. All four tested drugs showed a significant place preference compared with controls. Mice conditioned with MDPV (5 and 10 mg/kg) displayed a greater preference score compared to mice conditioned with amphetamine (5 and 10 mg/kg). Our findings show that mephedrone, methylone and MDPV produce CPP equal or higher than amphetamine strongly suggesting addictive properties. Given the public health concern of abuse, future pharmacological studies are necessary to fully understand the effects of these drugs.